Anti-Poverty, Community Organizing, and Learning in Response to the Mimico Secondary Plan - Abbe Edelson; Israt Ahmed; Martin Gerwin (Adult Education Research Conference, 2014)
This roundtable will provide an exploratory analysis of the informal and incidental learning gained by participants in and through the process of community-based organizing in Mimico, located within the City of Toronto, Canada. The authors posit that such learning is individual, collective, and intrinsic to the people’s participation.